Ctg^2 альфа-cos^2 альфа * ctg^2 альфа - cos^2 альфа

aaannnaaa1 aaannnaaa1    1   15.09.2019 00:40    0

Ответы
kiskaignatushkina kiskaignatushkina  07.10.2020 15:40
Ctg^2 альфа-cos^2 альфа * ctg^2 альфа - cos^2 альфа 

ctg^2 \alpha -cos^2 \alpha *ctg^2 \alpha -cos^2 \alpha = \\ \\ = ctg^2 \alpha (1 - cos^2 \alpha ) - cos^2 \alpha = \\ \\ =ctg^2 \alpha *sin^2 \alpha -cos^2 \alpha = \\ \\ = \frac{cos^2 \alpha }{sin^2 \alpha} *sin^2 \alpha -cos^2 \alpha = \\ \\ =cos^2 \alpha -cos^2 \alpha =0
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра